Targeting the epigenome in in-stent restenosis: from mechanisms to therapy - Xi Yang; Yanyan Yang; Junjie Guo; Yuanyuan Meng; Min Li; Panyu Yang; Xin Liu; Lynn Htet Htet Aung; Tao Yu; Yonghong Li (Elsevier, 2021)
Coronary artery disease (CAD) is one of the most common causes of death worldwide. The introduction of percutaneous revascularization has revolutionized the therapy of patients with CAD. Despite the advent of drug-eluting stents, restenosis remains the main challenge in treating patients with CAD. In-stent restenosis (ISR) indicates the reduction in lumen diameter after percutaneous coronary intervention, in which the vessel's lumen re-narrowing is attributed to the aberrant proliferation and migration of vascular smooth muscle cells (VSMCs) and dysregulation of endothelial cells (ECs). Increasing evidence has demonstrated that epigenetics is involved in the occurrence and progression of ISR. In this review, we provide the latest and comprehensive analysis of three separate but related epigenetic mechanisms regulating ISR, namely, DNA methylation, histone modification, and non-coding RNAs. Initially, we discuss the mechanism of restenosis. Furthermore, we discuss the biological mechanism underlying the diverse epigenetic modifications modulating gene expression and functions of VSMCs, as well as ECs in ISR. Finally, we discuss potential therapeutic targets of the small molecule inhibitors of cardiovascular epigenetic factors. A more detailed understanding of epigenetic regulation is essential for elucidating this complex biological process, which will assist in developing and improving ISR therapy.